The Relationship Between the Establishment of Aquatic Macrophytes and the Death of Mangroves in a South American Estuary: New Assessments of a Serious Environmental Problem - Sandretti-Silva, Giovanna [UNESP]; Teixeira, Larissa [UNESP]; Golec, Cláudia; Bornschein, Marcos R. [UNESP] (Springer Nature, 2023)
The Cananéia-Iguape estuarine-lagoon complex (ELCCI) in southeastern Brazil has been affected by the death of mangrove trees and the establishment of aquatic macrophytes (AMs). The main causes suggested for this phenomenon are reduced salinity and high nitrate concentrations; however, the possibility of a cause-and-effect relationship involving vegetation has also been raised. Aiming to enrich discussions about the catastrophic fate of the ELCCI, this study reviews the vegetation dynamics of the region proposed by Sampaio and colleagues and presents additional potential causes, effects, and conservation alternatives. We studied the ELCCI’s vegetation in 2000 and 2015 and analyzed orbital images produced in 2002–2022. We verified the death of mangroves and the invasion of 34 AMs within the mangroves and forming floating banks from the mid-2000s onward. The majority of AM species are native, and have low or no capacity to directly kill mangrove trees. We propose that the establishment of AMs and the death of mangroves in the ELCCI could be caused by an increased influx of freshwater enhancing AMs’ competitiveness and inducing vegetation replacement, or by an initial death of mangrove by some unknown factor (regressive ecological succession) followed by the entrance of AMs (progressive ecological succession). We suggest management actions to reduce freshwater input to increase salinity, since direct vegetation management is impractical.
Keywords: Bank of floating macrophytes; Estuarine-lagoon complex of Cananéia-Iguape; Valo Grande; Vegetation dynamics